2017
DOI: 10.1177/0886260517713711
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Group Threat, Perceived Injustice, and Self-Reported Right-Wing Violence: An Integrative Approach to the Explanation Right-Wing Violence

Abstract: The present study aims at explaining individual differences in self-reported political violence. We integrate key concepts from the field of criminology that are conceptually related to social identity theory (Flemish identity, feelings of group superiority, and ethnocentrism) and the dual process model on prejudice (perceived injustice, perception of threat, and right-wing authoritarianism). In our model, social identity concepts are hypothesized to play a mediating role between mechanisms derived from the du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 73 publications
(83 reference statements)
3
33
0
5
Order By: Relevance
“…Thus, chronic and situational threat and uncertainty, through increasing system justification, should increase participation in system-supportive (conservative) protest while undermining participation in system-challenging (progressive) protests. This framework is consistent with recent results showing that uncertainty and threat specifically increase right-wing-oriented radicalism: Pauwels and Heylen (2017) found that perceived in-group threat, through increasing authoritarianism, was related to participation in right-wing violence in a sample of young Belgians, and recent studies show that existential threat (Frischlich, Rieger, Hein, & Bente, 2015) and uncertainty (Rieger et al, 2017) increase interest in right-wing extremist groups' propaganda.…”
Section: Making the Connection: A System Justification Approach To supporting
confidence: 90%
See 1 more Smart Citation
“…Thus, chronic and situational threat and uncertainty, through increasing system justification, should increase participation in system-supportive (conservative) protest while undermining participation in system-challenging (progressive) protests. This framework is consistent with recent results showing that uncertainty and threat specifically increase right-wing-oriented radicalism: Pauwels and Heylen (2017) found that perceived in-group threat, through increasing authoritarianism, was related to participation in right-wing violence in a sample of young Belgians, and recent studies show that existential threat (Frischlich, Rieger, Hein, & Bente, 2015) and uncertainty (Rieger et al, 2017) increase interest in right-wing extremist groups' propaganda.…”
Section: Making the Connection: A System Justification Approach To supporting
confidence: 90%
“…Previous research has shown that some psychological dispositions that were hypothesized to underlie extremism are in fact predictive of certain ideological contents. For instance, the need to reduce threat and uncertainty, which was thought to drive all kinds of extremism (e.g., Hogg, Meehan, & Farquharson, 2010), is in fact related to right-wing ideologies (Jost et al, 2003;Jost et al, 2007) and right-wing radicalization in particular (Frischlich et al, 2015;Pauwels & Heylen, 2017;Rieger et al, 2017). Similarly, research indicates that there are substantial sociodemographic differences between left-wing and right-wing activists (Chermak & Gruenewald, 2015), suggesting that research should focus on the individual determinants of right-wing versus left-wing radicalization.…”
Section: Theoretical Implicationsmentioning
confidence: 99%
“…Among the causes for radicalisation, the literature distinguishes geopoliticalhistorical, social and personal factors (Beelman et al, 2018). Personal factors may be, among others, problematic personal characteristics (Besta et al, 2015;Campbell and Volhardt, 2014;Pauwels and Heylen, 2017) that can be complemented by such social ones as intra-family conflicts or the absence of integration on the labour market. It is mainly youngsters among 18 and 25 years old who correspond to that profile and may end up in prison and become or are already radicalised.…”
Section: Johan Lemanmentioning
confidence: 99%
“…In Belgium, there are also files written in French, which are followed by other professionals. 2 "On a sample of 1,200 individuals who left between 2012 and 2015 from Western countries to join Syria and Iraq, 14% are younger than 18 years old, 27% are between 18 and 21, 26% between 22 and 25, 17% between 26 and 29, 9% between 30 and 35 and 7% are 36 and more (Perliger and Milton 2016). If one qualifies "youngsters" as the category of age from 14 to 25 years old, they then represent 67% of the total.…”
Section: Concluding Considerationsmentioning
confidence: 99%
“…There is now a small but growing body of research showing that perceived racial discrimination leads to offending among minority groups, and it is therefore likely that other kinds of discrimination and injustice affect offending and antisocial conduct in general, not only in minority groups. De Waele and Pauwels (2016), Pauwels and Heylen (2017) and Doosje, Loseman and Van den Bos (2013) demonstrated that measures of perceived injustice negatively affected perceptions of personal respect (that is, the feeling that one is respected as a human being). Taken together, these findings suggest that perceived injustices will increase negative emotions (towards out-groups) that contribute to political violence.…”
Section: The Crystallization Of Discontent and Low Self-control As Camentioning
confidence: 99%